THE EFFECT OF DIFFERENT CONCENTRATIONS OF BENZOCAINE ON SOME BLOOD PARAMETERS OF CARP (CYPRINUS CARPIO L., 1758) - Basusta, Asiye; Ozcan, Mahmut (Parlar Scientific Publications (P S P), 2019)
Not only in growth and production conditions, but also in the laboratory, anesthesia is an important procedure required in many types of works including the times when an intervention with hands is needed and when the fish are prepared for shipping. Because of the fact that anesthesia with benzocaine is widely common, we wanted to investigate the biochemical changes in the blood and the serum of Cyprinus carpio L triggered by the application of un-lethal (25, 50, 75, 100 mg/L) doses of benzocaine (ethyl amino benzoate). For this purpose, we picked the common carp (Cyprinus carpio) which were roughly in 30 g weight and 4.9 cm in length. All measurements were performed in triplicates. During the study, in total, 150 fish were examined. In the groups upon which 25 and 50 mg/L doses of benzocaine were applied, there was no difference in blood levels of Hematocrit, Leucocratic, Erythrocyte, Leucocyte, Hemoglobin, Adherent, Phagocytic ratio, and MCV compared to the control group while in the doses of 75 and 100 mg/L an increase in all these parameters was observed. Additionally, there has been no change in serum protein levels when the fish were exposed to 25, 50, 75 and 100 mg/L doses of benzocaine.
Keywords: Carp; Cyprinus carpio; Benzocaine; Blood Parameters